Novel framework for hidden data in the image page within executable file using computation between advanced encryption standard and distortion techniques - Naji, Ahmed Wathik; Hameed, Shihab A.; Al-Khateeb, Wajdi Fawzi Mohammed; O-Khalifa, Othman; Zaidan , A. A.; Gunawan, Teddy Surya (LJS Publisher and IJCSIS Press, 2009)
The hurried development of multimedia and internet allows for wide distribution of digital media data. It becomes much easier to edit, modify and duplicate digital information. In additional, digital document is also easy to copy and distribute, therefore it may face many threats. It became necessary to find an appropriate protection due to the significance, accuracy and sensitivity of the information. Furthermore, there is no formal method to be followed to discover a hidden data. In this paper, a new information hiding framework is presented.The proposed framework aim is implementation of framework computation between advance encryption standard (AES) and distortion technique (DT) which embeds information in image page within executable file (EXE file) to find a secure solution to cover file without change the size of cover file. The framework includes two main functions; first is the hiding of the information in the image page of EXE file, through the execution of four process (specify the cover file, specify the information file, encryption of the information, and hiding the information) and the second function is the extraction of the hiding information through three process (specify the stego file, extract the information, and decryption of the information).